HOW SOCIAL FACTOR DETERMINE INDIVIDUAL TAXPAYERS’ TAX COMPLIANCE BEHAVIOUR IN MALAYSIA? - Nivakan, Sritharan; Salawati, Sahari; Cheuk, Sharon Choy Sheung (2020)
The aim of this study is to clarify the role of social factors on individual taxpayers’ tax compliance behaviour in Malaysia. Studies with similar topics express the fact that there still exists a gap in the developing countries that impact the decision making on tax compliance. Malaysia is a multi-racial and cultural country with social factors to impact on tax compliance. Some of the factors impacting are cultural impact, political affiliation, and religiosity, which are considered to be playing an important role in individual tax compliance behaviour. The researcher used a survey method of research design. For that the population targeted was the individual taxpayers across Malaysia. A sample of 419 respondents had been taken for this study, using a convenient sampling method. Pearson correlation and multiple regression analysis had been employed to analyse the data. The outcome of the study reveals that changes in government policies, referral groups, the role of LHDN, and political affiliation are the main important variables that determine individual taxpayers’ tax compliance behaviour. This paper studied social factor variables, which finally fills the gap that existed in the literature and helps tax administration to develop effective compliance risk treatment.